Fatigue performance of cold spray deposits: Coating, repair and additive manufacturing cases. (October 2020) - Bagherifard, Sara; Guagliano, Mario
Highlights: Current state of the art on fatigue performance of cold spray deposits is reviewed. Uniform coatings, local coatings, and additive manufacturing cases are covered. Recent advancements and existing challenges are described. Future perspectives and promising trends are discussed. Abstract: Cold spray technology has recently gained much attention for applications beyond its primary cause of protective coating deposition. It has found its way for depositing thin films for surface functionalization, thick coatings for geometrical restoration, and has exhibited a high potential for additive manufacturing. As cold spray paves its way towards more structural applications, evaluating its performance under cyclic loading is of significant importance. Herein, the current state of the art on the contribution of various forms of cold spray deposits to fatigue strength is reviewed. Future perspectives for enhancing their structural integrity and promising trends are discussed.